One-punch man. 19, All my cabbage - ONE, 1986- (Shonen Jump manga., 2020)
The Monster Association has kidnapped Tareo, the boy who admires Garo, and now Garo finds himself plunging headfirst and alone into the heart of the Monster Association's hideout. Meanwhile, the Hero Association pushes forward with its operation to rescue Waganma, while Genos and the others are living it up enjoying hot pot at Saitama's place!